Synthesis, Characterization, Biological Activity Studies of Schiff Bases and 1,3-Oxazipene Derived from 1,1 -Bis (4-aminophenyl) -4-Phenyl Cyclohexane - Nief, Olfat A.; Salman, Hussein N.; Ahamed, Luma S. (Iraqi Journal of Science, 2021)
A series of new Schiff bases and 1, 3-Oxazepine derivatives have been synthesised from condensation compound (1,1 -bis (4-aminophenyl) -4-phenyl cyclohexane [C1] with different aromatic aldehydes in the presence of catalytic glacial acetic acid to produce the Schiff bases [2-4]. These Schiff bases were reacted with maleic anhydride and phthalic anhydride in dry benzene to give seven-membered heterocyclic ring derivatives [5-10]. The structure formula of these compounds were confirmed by using FT-IR, (1H and 13C) NMR spectroscopy. The synthesized compounds were screened for their anti‐bacterial activity using ampicillin as a standard drug.